2021
DOI: 10.25259/ijms_177_2020
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and navigating conundrums in setting up an obstetrics and gynecology coronavirus disease facility in a pre-existing tertiary care hospital – An Indian perspective

Abstract: India at present has 145,779 active coronavirus disease (COVID) cases and 8884 deaths. Being the largest tertiary care health facility under Delhi Government, our center was designated as a 2000 bedded dedicated COVID hospital. In addition to establishing areas for COVID management, COVID Obstetrics and Gynecology area requires a dedicated set up for delivering women, an operating room, and a neonatal care unit. A phased evacuation plan begins by curtailing non-emergency services and postponing elective surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Level 2 delay in our study was most commonly due to being declined at a previous center. During the pandemic, many hospitals in our city (both private and public sector) were converted into COVID hospitals and their obstetric facilities were shut down (Dhiman et al,2021). Although the inpatients in these hospitals at the time of conversion were referred to other hospitals, the pregnant women booked/registered at these centers were neither guided appropriately, nor a linkage was established with other centers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Level 2 delay in our study was most commonly due to being declined at a previous center. During the pandemic, many hospitals in our city (both private and public sector) were converted into COVID hospitals and their obstetric facilities were shut down (Dhiman et al,2021). Although the inpatients in these hospitals at the time of conversion were referred to other hospitals, the pregnant women booked/registered at these centers were neither guided appropriately, nor a linkage was established with other centers.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, many women had a delay in being attended in the casualty due to overcrowding. There was a shortage of manpower as many healthcare professionals were suffering from the infection (Dhiman et al,2021). A meta-analysis on level 3 delay in developing countries (Knight et al, 2013) revealed various barriers in care: skilled health professionals (86%), availability of drugs/ other components (65%), staff shortages (60%), and low staff motivation (44%).…”
Section: Resultsmentioning
confidence: 99%
“…These SOPs should allow for swift revisions, if warranted, within a 3-4week timeframe to effectively respond to evolving pandemic dynamics. 14 The preparedness evaluation for health facilities embraces multiple facets, including the availability of personal protective equipment (PPE), functional blood banks, proficient surgical teams, nursing support, sterile equipment, room capacity, negatively pressurized operating rooms, specialized treatment spaces, and prompt emergency management. Effective scheduling, in accordance to available resources and individual patient needs, must be orchestrated across the hospital system to ensure patient-specific care.…”
Section: Resultsmentioning
confidence: 99%